The political career of Dr. Pedro G. Trono (1951-1969). - Talledo, Joelleni G (2003.)
This is a study about the political career of Dr. Pedro G. Trono who served as a Board Member of the Province of Iloilo from 1951-1953 and as a congressman of the First District of Iloilo from 1954-1969. This research aims to 1.)Determine the reasons and circumstances that made Dr. Trono enter politics, 2.) Determine the factors that favored his career, 3.) Find out the problems and difficulties that he encountered and how he was able to handle them, and 4.) Find out his achievements and to analyze their importance, to the people of the First District of Iloilo. The researcher interviewed key-informants and other people knowledgeable about this topic., It was found out that Dr. Trono had been influenced by his father to enter politics aside from the fact that he wanted to serve the people of Iloilo. Several factors led to his victory i the elections. He had effective political resources, efficient campaign strategies and good socio-economic background. He also came across problems regarding health, education and livelihood during his political career. Thus, he was able to establish a hospital, a school and other programs that alleviated the condition of the people in Iloilo especially those in First District.
Research Project (Undergraduate, Bachelor of Arts in History) College of Arts and Sciences, UP Visayas, Miagao, Iloilo.
Keywords: Trono, Pedro -- Political Career